PHYSICAL-CHEMICAL AND THERMODYNAMIC CHARACTERISTICS OF KAOLIN CLAY OF THE CHOKO-BULAK DEPOSIT AT DIFFERENT TEMPERATURES DESTRUCTION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The chemical matrix of unfired kaolin clay from the Choko-Bulak deposit was compiled and thermodynamic modeling of its destruction was carried out over a wide range of temperature changes. The physicochemical and thermodynamic parameters of a multicomponent complex clay system were calculated. The concentration distribution of Al, Si, Fe, Ca, Mg, H, O-containing components, active particles and condensed phases at the maximum entropy of the system has been established. Temperature limits for the formation and transformation of various aluminum-containing substances have been identified.
Keywords: kaolin, clay, destruction, oxide, hydroxide, aluminum.